ENDOGAMY MARRIAGE MITOCHONDRIAL DNA VARIATION OF NORTH CIGINTUNG GARUT ISOLATES - Satiyarti, Rina Budi; Anggita, Rindu (UNIVERSITAS ISLAM NEGERI RADEN INTAN LAMPUNG, 2018)
Mitochondrial DNA (mtDNA) has an unique genetic sequences which made its different from nuclear DNA. MtDNA is maternally inherited without recombination, and it has higher mutation rate rather than nuclear DNA. D-loop is an noncoding area in mtDNA which has highest polymorphism among mtDNA. The objective of this research is to study about nucleotide variation in D-Loop area from people who has endogamy marriage. The subject is four generation of maternally inherited. The research steps are sample collection, DNA template preparation, mtDNA amplification, agarose gel electrophoresis, sequencing analysis and homology analysis. The amplification of D-Loop fragment has 0,9 kb in size. Homology analysis showed fifty varians nucleotides.